Utilization of bamboo as a low cost structural material. - Abang Ali, Abang Abdullah (1983)
The bamboos are very important plants in many parts of Asia and the world. Despite being an easily replenishable material having some noted strengths, bamboo has not been fully utilized as a building material. However with the current rate of consumption of the traditional materials by the building industry, it is anticipated that bamboo will become increasingly important in the near future. Mechanical testing of local species of bamboo is being carried out and a pilot project on cultivation of the various species has been started at Universiti Pertanian Malaysia. This paper presents the work which is being carried out at the University on the utilization of bamboo as a low-cost material of construction.